Disparity in Law Enforcement in The Crime of Electronic Information Theft - Iqbal Maulana Ghozi; Endang Sutrisno (Jurnal Syntax Transformation, 2026)
The rapid digital transformation of society has increased cybercrime incidents significantly, particularly electronic information theft, raising concerns over legal certainty and equal law enforcement in Indonesia. This study aims to analyze disparities in the enforcement of electronic information theft cases within the Indonesian criminal justice system. A normative juridical method with a qualitative descriptive approach was employed, using literature study, statutory analysis, and comparative case review. The findings show that enforcement disparities are influenced by ambiguous legal norms, uneven digital forensic infrastructure, differences in judges' digital literacy, and centralized case handling in major cities. Case comparisons between Banjarmasin, South Jakarta, and Yogyakarta reveal significant sentencing variations for similar cybercrime acts. These inconsistencies indicate the absence of standardized sentencing guidelines and unequal evidentiary capacities across jurisdictions. Consequently, such disparities undermine legal certainty and public trust in cyber law enforcement. The study concludes that structural reforms, including the harmonization of legal interpretation, the standardization of sentencing guidelines, and the equitable distribution of forensic technology, are urgently needed to ensure fair and consistent justice in electronic information crime cases. These reforms are essential to strengthen legal certainty, deterrence, and public confidence in Indonesia's digital justice system and to support equitable access to justice across regions nationwide.